A Meta-Analysis of Early, Mid-term and Long-Term Mortality of On-Pump vs. Off-Pump in Redo Coronary Artery Bypass Surgery - Zhang, Shicheng; Huang, Siyuan; Tiemuerniyazi, Xieraili; Song, Yangwu; Feng, Wei (Frontiers in Cardiovascular Medicine, 2022)
We aimed to compare the early, mid-term, and long-term mortality between on-pump versus off-pump redo coronary artery bypass grafting (CABG). We conducted a systematic search for studies comparing clinical outcomes of patients who underwent on-pump vs. off-pump redo CABG. We pooled the relevant studies quantitively to compare the early (perioperative period, whether in hospital or within 30 days after discharge), mid-term(≥1year and ＜5 years), and long-term (≥5year) mortality of on-pump versus off-pump redo CABG. A random-effect model was applied when there was high heterogeneity (I2 > 50%) between studies. Otherwise, a fixed-effect model was utilized. After systematic literature searching, 22 studies incorporating 5197 individuals (3215 in the on-pump group and 1982 in the off-pump group) were identified. A pooled analysis demonstrated that compared with off-pump redo CABG, on-pump redo CABG was associated with higher early mortality (OR 2.11, 95%CI: 1.54-2.89, P<0.00001). However, no significant difference was noted in mid-term mortality (OR 1.12, 95%CI: 0.57-2.22, P=0.74) and long-term mortality (OR 1.12, 95%CI: 0.41-3.02, P=0.83) between the two groups. In addition, the complete revascularization rate was higher in the on-pump group than the off-pump group (OR 2.61, 95%CI: 1.22-5.60, P=0.01). In conclusion, the off-pump technique is a safe and efficient alternative to the on-pump technique, with early survival advantage and similar long-term mortality to the on-pump technique in the setting of redo CABG, especially in high-risk patients.